The Aeroplane Speaks - Barber, H. (Horatio), 1875-1964 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Aeroplane Speaks" by H. Barber is an insightful treatise about aviation, aimed at both the layman and the experienced pilot, written during the early 20th century. The book seeks to demystify the aeroplane's operation by presenting its principles and components in a conversational format, personifying elements such as Lift, Drift, and Efficiency as characters engaging in dialogue. At the start of the book, the setting is a Royal Flying Corps School for Officers, where the elementary principles of flight express their grievances about being misunderstood. The narrative unfolds with these principles discussing the mechanics behind flight, including Lift, Thrust, and Drift, while introducing the various roles they play in allowing an aeroplane to fly successfully. The engaging dialogue serves not only to educate the reader about aerodynamics but also emphasizes the intricate relationships and compromises needed in design and operation, setting the stage for deeper exploration in subsequent chapters. (This is an automatically generated summary.)
Release date is 1997-02-01
Produced by Charles Keller, and David Widger
Keywords: Airplanes